PENINGKATAN MOTORIK HALUS ANAK MELALUI KEGIATAN KOLASE BERBASIS BIJI DI TK DZAKIYYAH PALEMBANG - Asdar, Asdar; Rosdia, Eva (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2024)
The activities carried out in the research aim to improve the development of children's motor skills in playing with grain media collage at TK Dzakiyyah Palembang. The research was conducted at TK Dzakiyyah Palembang with 15 students. From the results of observations at TK Dzakiyyah Palembang, it was found that 49% of collage skills were still lacking. These results were carried out by teachers on children's activities before and after improving children's development activities in collage activities, reaching an average of 49%, so improvements were made in cycle I of fine motor activities through media collage in the form of seeds, which increased to an average of 68%, followed by cycle II, media collage in the form of kuaci seeds. , coriander seeds, rice seeds and ice beans as well as picture patterns on worksheets that have varying colors so that there is an increase of 10% and the average success value reaches 78% with children developing very well in accordance with expectations, namely 93% so that the collage ability grain media is greatly increased. So the conclusion is that using media materials in the form of seeds can develop students' fine motor skills so that they can be used as media that can increase collage activities for children.